2017
DOI: 10.3857/roj.2017.00465
|View full text |Cite
|
Sign up to set email alerts
|

Refining prognostic stratification of human papillomavirus-related oropharyngeal squamous cell carcinoma: different prognosis between T1 and T2

Abstract: PurposeTo validate the 8th edition of the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) TNM staging system for human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) and investigate whether a modified classification better reflects the prognosis.Materials and MethodsMedical records of patients diagnosed with non-metastatic HPV-related OPSCC between 2010 and 2016 at a single institution were retrospectively reviewed. HPV status was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Mizumachi et al (31) demonstrated similar results, reporting a significant difference in 3-year overall survival rate between stages I–II and III. Although T-staging is considered more influential for clinical outcome than N-staging in HPV-related OPSCC (18), we did not find a significant association between T-staging and PFS in the multivariate analysis. This may be due to the relatively small number of T3 and T4 cases (n = 33) and progressive T3 and T4 cases (n = 7).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Mizumachi et al (31) demonstrated similar results, reporting a significant difference in 3-year overall survival rate between stages I–II and III. Although T-staging is considered more influential for clinical outcome than N-staging in HPV-related OPSCC (18), we did not find a significant association between T-staging and PFS in the multivariate analysis. This may be due to the relatively small number of T3 and T4 cases (n = 33) and progressive T3 and T4 cases (n = 7).…”
Section: Discussioncontrasting
confidence: 80%
“…The other method used was tumor HPV DNA detection by polymerase chain reaction (PCR)/DNA chip scanning, which can detect 43 subtypes of HPV (high-risk subtypes 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, 73, and 82 and other lower or undetermined risk subtypes). HPV-related OPSCC was diagnosed when the results of either p16 or HPV DNA PCR were positive (18).…”
Section: Methodsmentioning
confidence: 99%
“…Use of p16 IHC alone, as per TNM8 staging guidelines, demonstrated improved prognosis in our study but with overlap of stage I and II cancers as reported in some but not all studies. 2125 As part of an ‘organ preservation’ strategy the primary treatment modality for the majority of patients with OPSCC has been radiotherapy with and without concurrent chemotherapy and as such TNM8 staging criteria has been evaluated primarily in these patients. 13,20 Notably our study and other studies demonstrating overlap of stages I and II included cohorts where the majority of patients received surgery and where use of pathologic TNM8 staging was recommended instead of clinical.…”
Section: Discussionmentioning
confidence: 99%
“…P16 immunohistochemistry was performed using CINtec p16 histology (anti-p16 INK4a mouse monoclonal antibody and immunohistochemical detection kit; Roche MTM Laboratories, Heidelberg, Germany) and HPV DNA detection was performed by 16,18,31,33,35,39,45,51,52,56,58,59,68,73,82, and other lower or undetermined risk subtypes) 37 . HPV-positive OPSCC was diagnosed based on the positive results of either p16 or HPV DNA PCR 38 .…”
Section: Study Populationmentioning
confidence: 99%